(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2012)
The aim of this paper is to carry out a descriptive analysis about the situation of Spanish firms regarding to their technological endowment, reviewing differen treports and statistics published by a wide range of institutions. Starting from a proposal about how to classify these technologies, several data related to their implementation in the firm and their perceived impacts on different areas are shown andanalyzed, according to two complementary perspectives, an aggregate approximation and a review of several cases of Spanish firms. These examples are useful to show the practical impacts of certain technologies. Finally, some conclusions on the implementation of ICT and future research lines on this matter are presented.